Congenital Nephrotic Syndrome and the Heart: Lest We Forget!. Issue 3 (September 2021) - Bhattacharya, Deepanjan; Kaur, Anit; Dawman, Lesa; Tiewsoh, Karalanglin
We report a 2-month-old girl, presenting with anasarca in the early infancy, and was diagnosed to have congenital nephrotic syndrome. In view of a systolic murmur, echocardiography was done which revealed ostium secundum atrial septal defect and branch pulmonary artery stenosis. Genetic analysis was suggestive of single base pair duplication, resulting into frame shift mutation of NPHS1 (nephrin) gene.